2009
DOI: 10.1007/s00535-009-0006-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of hedgehog signaling during gastric regeneration

Abstract: The above results suggest that hedgehog signaling is involved in the differentiation of gastric progenitor cells during the gastric ulcer repair process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 30 publications
(32 reference statements)
2
34
0
Order By: Relevance
“…By contrast, upregulation of HH signaling by conditional removal of Ptch1 in adult colonic mesenchyme results in the depletion of the epithelial precursor cell pool due to premature differentiation (van Dop et al, 2009). Furthermore, HH signaling has been found to be downregulated during repair following gastric ulcer induction, whereas inhibition of SMO via cyclopamine treatment of injured mice further inhibits gastric progenitor cell differentiation (Kang et al, 2009). In mouse models of HH pathway inhibition, atrophy of the small intestinal villi is observed resulting from the loss of villus smooth muscle cells, which is also accompanied by inflammation and an increase in proliferation in the epithelial compartment (van Dop et al, 2010;Zacharias et al, 2010).…”
Section: Respiratory and Gastrointestinal Systemsmentioning
confidence: 99%
“…By contrast, upregulation of HH signaling by conditional removal of Ptch1 in adult colonic mesenchyme results in the depletion of the epithelial precursor cell pool due to premature differentiation (van Dop et al, 2009). Furthermore, HH signaling has been found to be downregulated during repair following gastric ulcer induction, whereas inhibition of SMO via cyclopamine treatment of injured mice further inhibits gastric progenitor cell differentiation (Kang et al, 2009). In mouse models of HH pathway inhibition, atrophy of the small intestinal villi is observed resulting from the loss of villus smooth muscle cells, which is also accompanied by inflammation and an increase in proliferation in the epithelial compartment (van Dop et al, 2010;Zacharias et al, 2010).…”
Section: Respiratory and Gastrointestinal Systemsmentioning
confidence: 99%
“…9 Hh signaling is also critical for regeneration of several other organs such as stomach and exocrine pancreas. 11,12 In several of the tissues in which Hh is involved in renewal, pathway mis-activation has been linked to tumor formation. A similar role for Hh signaling in the development of salivary gland cancer has, so far, not been investigated.…”
mentioning
confidence: 99%
“…Hh molecules (Sonic, Indian, and Desert Hedgehog) are important signaling proteins that play critical roles in the development and differentiation of many tissues and maintenance of adult SCs and CSCs [85,86]. Hh signaling is involved in the differentiation of gastric progenitor cells into mucous cells and parietal cells during the gastric ulcer repair process [85].…”
Section: Hedgehog Pathwaymentioning
confidence: 99%
“…Cyclopamine, a specific inhibitor of Hh signaling, decreased the number of cells with the pit phenotype [96]. A recent study showed that cyclopamine significantly inhibited the differentiation of mucous cells and parietal cells during the gastric regeneration process; however, it did not affect their proliferation [85]. Further clues elucidating abnormal Shh signaling in the maintenance of GCSCs arose from a study by Song and coworkers, who isolated tumor sphere cells that showed an increased self-renewal capacity and chemoresistance, expressed CSC-related markers (CD44, CD24, and CD133), and had higher tumorigenic capacity in vivo.…”
Section: Hedgehog Pathwaymentioning
confidence: 99%
See 1 more Smart Citation